Effect of ether glycerol lipids on interleukin-1β release and experimental autoimmune encephalomyelitis. (January 2016) - Boomkamp, Stephanie D.; Byun, Hoe-Sup; Ubhi, Satvir; Jiang, Hui-Rong; Pyne, Susan; Bittman, Robert; Pyne, Nigel J.
Highlights: The glycerol lipid77-6 stimulated IL-1β release from macrophages. This involves activation of the inflammasome and caspase 1. The glycerol lipid56-5 promotes EAE disease progression. This is independent of the inflammasome and might involve modulation of PAF signalling. Glycerol lipids might be a starting point for development of anti-inflammatory drugs. Abstract: We have assessed the effect of two ether glycerol lipids, 77-6 ((2 S, 3 R )-4-(Tetradecyloxy)-2-amino-1, 3-butanediol) and56-5 (( S )-2-Amino-3- O -hexadecyl-1-propanol), which are substrates for sphingosine kinases, on inflammatory responses. Treatment of differentiated U937 macrophage-like cells with77-6 but not56-5 enhanced IL-1β release; either alone or in the presence of LPS. The stimulatory effect of sphingosine or77-6 on LPS-stimulated IL-1β release was reduced by pretreatment of cells with the caspase-1 inhibitor, Ac-YVAD-CHO, thereby indicating a role for the inflammasome. The enhancement of LPS-stimulated IL-1β release in response to sphingosine, but not77-6, was reduced by pretreatment of cells with the cathepsin B inhibitor, CA074Me, indicating a role for lysosomal destabilization in the effect of sphingosine. Administration of56-5 to mice increased disease progression in an experimental autoimmune encephalomyelitis model and this was associated with a considerable increase in the infiltration of CD4 + T-cells, CD11b + monocytes and F4/80 + macrophages in the spinal cord.56-5 and77-6 were without effect on the degradation of myc-tagged sphingosine 1-phosphate 1 receptor in CCL39 cells. Therefore, the effect of56-5 on EAE disease progression is likely to be independent of the inflammasome or the sphingosine 1-phosphate 1 receptor. However, 56-5 is chemically similar to platelet activating factor and the exacerbation of EAE disease progression might be linked to platelet activating factor receptor signaling.